HUBUNGAN PROFESIONALISME, IKLIM SEKOLAH, DAN INTEGRITAS DENGAN KINERJA GURU SMP NEGERI DI KOTA ADMINISTRASI JAKARTA TIMUR (2015) - Nani Dewi Sunengsih (Jurnal Manajemen., 2015)
The study aims to analyze the relationship between professionalism, schoolclimate, teacher performance and integrity of the Junior High School in East Jakarta. The survey was conducted in this study with a sample of 100 teachers with simple random sampling technique. Data were analyzed using correlational technique. The research findings are as follows. (1) There is a relationship between the professionalism and the performance. In other words, the higher the professionalism of teachers will be better performance. (2) There is a relationship between school climate and the performance. In other words, the higher the school climate will be better teacher performance. (3) There is a relationship between the integrity and the performance. In other words, the higher the integrity of the teacher so the higher the performance. (4) There is a relationship between professionalism, school climate, and integrity together with the performance. In other words, the higher the professionalism of teachers, school climate, and integrity of teachers together so the higher the performance.